Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai di MAN 2 Kota Malang - Muhammad Djordan Al Sulthoni; Syahirul Alim (Universitas Batanghari Jambi, 2023)
Human Resources (HR) is very important in an organization because HR is a component that can determine success in a company. All employees in the school are an important component for improving the quality of education and in preparing future candidates for the nation, therefore this study aims to determine the effect of work motivation and work environment on employee performance at MAN 2 Malang City. The type of research used is quantitative research. This research was conducted at MAN 2 Malang City with a population of 127 employees and a sample of 56 employees. Data collection techniques in this study are observation and questionnaires. The result of the calculated t value on the Work Motivation variable (X1) is 5.587 while the t table value is 1.672. Then it is known that t count > t table, with sig. 0.001 <0.05. So that Ho is rejected and Ha is accepted, which means that the work motivation variable has a significant influence on employee performance and the results of the calculated t value in the Work Environment variable (X2) are 2.880 and the t table value is 1.627. Therefore, it can be seen that t count < t table, with a sig value of 0.006 > 0.05. So that Ho is rejected and Ha is accepted, then the work environment variable has a significant influence on employee performance. The result on the calculated f value obtained is 390.873 while the f table value is (3.17). It can be seen that f count is 390.873 > f table 3.17 with a significant level of 0.001 <0.05, therefore this regression model can be used for employee performance variables at MAN 2 Malang City. it can be said that the variables of work motivation and work environment have a significant effect on employee performance simultaneously. So the results of this study are also in accordance with the theory that has been explained that work motivation can direct the power and potential of an employee to be able to improve his performance. So these results are also in accordance with the theory that has been explained that the existing infrastructure in the work environment of an employee is able to make the desire to work and can produce very good work.